Competitive Equilibria Under Uncertainty - Stigum, Bernt P. (Quarterly Journal of Economics, 1969)
I. Introduction, 533. — II. The Arrow-Debreu models of consumer and entrepreneurial choice under uncertainty, 534. — III. Consumer choice under uncertainty, 538. — IV. Entrepreneurial choice under uncertainty, 543. — V. The existence of a competitive equilibrium under uncertainty, 547. — VI. Concluding remarks, 553. — Appendix, 556.